Lifestyles and habits in young people: analysis of Italian National Institute of Statistics database: Lifestyles and habits in young Italian people - Fabbian, Fabio; Rodríguez-Muñoz, Pedro Manuel; Cappadona, Rosaria; Di Simone, Emanuele; Di Muzio, Marco; Rodríguez-Borrego, Maria Aurora; López-Soto, Pablo Jesús (Progress in Nutrition, 2021)
The aim of this study was to evaluate healthy and unhealthy habits of young Italian people. A descriptive cross-sectional study was carried out on young Italian people, aged 15 to 34 years, taking into consideration data collected by Italian National Institute of Statistics (ISTAT) in 2008. Italy was divided in four areas, north, centre, south, and islands. The variables were grouped into the following categories: sociodemographic variables, overweight and obesity, alcohol and tobacco use, food consumption, and physical activity. ISTAT showed that 13% of young people in Italy were overweight, and 2.1% obese, 20% were smokers, being the highest percentage in the centre of Italy, and in men; 12% consumed alcohol more than once a week, being beer the favourite beverage. Alcohol consumption was higher in north of Italy. Nearly 80% of young Italian people had breakfast properly. Men consumed more meat than women, and women consumed more vegetables than men. Both men and women had equal consumption of cheese and fish. Physical activity was practiced by 37% of young people, prevailing in the north of the Country. ISTAT data suggest that healthy profile of young Italian persons should be taken into consideration in order to prevent development of noncommunicable diseases.